Oxidative stress coping capacity (OSC) value: Development and validation of an in vitro measurement method for blood plasma using electron paramagnetic resonance spectroscopy (EPR) and vitamin C - Nibbe, Pauline; Schleusener, Johannes; Siebert, Silas; Borgart, Richard; Brandt, Doreen; Westphalen, Ronja; Schüler, Nadine; Berger, Bastian; Peters, Eva M.J.; Meinke, Martina C.; Lohan, Silke B. (Free radical biology & medicine, 2023)
Oxidative stress as a driver of disease is reinforcing the trend towards supplementation with antioxidants. While antioxidants positively influence the redox status when applied at physiological doses, higher concentrations may have pro-oxidative effects. Precise assessment methods for testing the supply of antioxidants are lacking. Using in-situ-irradiation as stressor and electron paramagnetic resonance (EPR) spectroscopy as readout system for formed radicals, a stress response assessment method was developed, using protein solutions and plasma samples from transfusion medicine. The method was validated in a double-blind placebo-controlled in vivo cross-over pilot study in blood plasma samples of individuals before and after vitamin C supplementation. Reference measurements were performed for the exogenous antioxidants β-carotene and vitamin C, and glutathione as an endogenous representative. Malondialdehyde was studied for oxidative stress indication. Protein solutions without antioxidants showed a linear increase in radical concentration during irradiation. The in-vitro-addition of vitamin C or plasma samples from subjects displayed two slopes (m1, m2) for radical production, whereby m1 represented the amount of antioxidants and proteins, m2 only the protein content. These two slopes in combination with the intervening transition area (T) were used to calculate the oxidative stress coping capacity (OSC), which correlated positively with vitamin C concentration in blood plasma, while oxidative stress biomarkers showed only fluctuations within their reference ranges. Furthermore, a selective radical quenching mechanism for vitamin C was observed: the proportion of reactive oxygen species (ROS) in the plasma samples was degraded in dependence to the vitamin C concentration ingested. The proportion of lipid oxygen species (LOS) remained stable while the ascorbyl radical increased with higher vitamin C intake. OSC may represent a sensitive method to detect treatment effects on the redox status in vivo in future validation and treatment studies, and potentially in clinical routine. [Display omitted] •Development of a method for estimating the entire redox status in blood plasma.•Oxidative stress coping capacity (OSC) value to assess redox homeostasis.•Validation by a double blind place controlled cross-over in-vivo pilot study.•Significant positive correlation between blood vitamin C concentration and OSC values.•OSC is more sensitive to short-term supplementation than typical stress biomarkers and can reveal even slight differences in redox homeostasis.